Phenolic compounds and antioxidant capacities of bayberry juices - Fang, Zhongxiang; Zhang, Y.; Lü, Y.; Ma, G.; Chen, J.; Liu, D.; Ye, X. (Elsevier BV, 2009)
Phenolic compounds and antioxidant capacities of bayberry juices from 14 cultivars were investigated. HPLC-DAD and Folin-Ciocalteu methods were used for the analysis of the phenolic compounds. Biqi had the highest content of total flavonols (56.75 ± 4.68 mg/l), Wuzi had the highest content of phenolic acids (30.1 ± 0.05 mg/l), and Lizhizhong had the highest content of anthocyanins (514 ± 46.1 mg/l) and total phenolics (1055 ± 9.32 mg GAE/l). The FRAP and ABTSradical dot+ assay indicated that bayberry juices possessed considerable antioxidant activities, and all the analysed phenolic components contributed to the antioxidant capacities. The results also showed that bayberry juices from red coloured cultivars possessed higher contents of phenolic compounds than those from white coloured cultivars. The higher antioxidant capacities of red bayberry juices implied that they might be potential resources for the development of functional drinks. © 2008.